Regulatory competition and forbearance: Evidence from the life insurance industry - McShane, Michael K.; Cox, Larry A.; Butler, Richard J. (Journal of Banking & Finance, 2010)
Regulatory separation theory indicates that a system with multiple regulators leads to less forbearance and limits producer gains while a model of banking regulation developed by Dell’Ariccia and Marquez (2006) predicts the opposite. Fragmented regulation of the US life insurance industry provides an especially rich environment for testing the effects of regulatory competition. We find positive relations between regulatory competition and profitability measures for this industry, which is consistent with the Dell’Ariccia and Marquez model. Our results have practical implications for the debate over federal versus state regulation of insurance and financial services in the US.